Pengaruh Penerapan Budaya Tri Hita Karana, Kecerdasan Emosional, Keadilan Prosedural, Dan Internal Control Terhadap Kecenderungan Kecurangan Akuntansi Pada Lembaga Perkreditan Desa (Lpd) Se-Kecamatan Nusa Penida - dwi astana, i kadek yogi; Sumadi, Ni Komang; Samtika Putra, I Putu Deddy (Hita Akuntansi dan Keuangan, 2023)
The goal of this reserach was to help examining the influence of the implication of the Tri Hita Karana culture, emotional intelligence, procedural justice, and internal control toward tendency of fraud in accounting in institutions of village credit (LPD) throughout the Nusa Penida sub-district. This study was done at LPDs through  the Nusa Penida sub-district with a total 45 LPDs populations with a sample size of 135 people. The sample was examined by purposive method of sampling, namely several determined criteria. Data collection techniques applying a questionnaire then performed with analysis of multiple linear regression, test the coefficient of determination and also t test. Then the results stated that (1) the implication of the Tri Hita Karana culture gives no significant effect toward tendency of fraud of accounting, (2) emotional intelligence gives such a negative and also significant effect toward tendency of accounting fraud, (3) procedural justice gives such a significant and also negative influence toward tendency of fraud of accounting, (4 ) internal control gives such a negative and significant effect toward tendency of fraud of accounting. The advice given is that it is hoped that all LPDs in the Nusa Penida sub-district will be able to apply the Tri Hita Karana culture in LPDs properly. By implementing the tri hita karana culture, it will affect a good cultural climate which will also create good behavior for everyone in the LPD environment, so as to reduce accounting fraud.